P‐108: Eye‐Tracking IPS 3D Display with a Liquid Crystal Barrier. Issue 1 (June 2015) - Oka, Shinichiro; Koito, Takeo; Yang, Yingbao; Sugiyama, Hiroki; Hyodo, Yosuke; Maeda, Yuji; Ochiai, Takahiro; Takahashi, Tomoyuki; Komura, Shinichi
Abstract : We have developed a new eye‐tracking IPS 3D display with a liquid crystal active barrier. A new IPS electrode and active barrier were developed to facilitate 3D wide viewing angle characteristics, low crosstalk and a smooth moving barrier in a 3D eye‐tracking system. The important parameters for the eye‐tracking 3D display are low crosstalk, fast response time of the LC barrier, and wide viewing angle of the image, to show a wide and smooth 3D image. In this paper, a new active barrier electrode, a new liquid crystal material, and a new IPS electrode are introduced for 3D displays using an eye‐tracking system.